Affect and eating behavior in obese adults with and without elevated depression symptoms - Goldschmidt, Andrea B. (2013)
OBJECTIVE: Although there is a modest relation between obesity and depression, mechanisms that contribute to this co-occurrence are unclear. This study examined mood and eating behavior among obese adults with and without elevated depression symptoms. METHOD: Obese adults (N=50) were subtyped according to a Beck Depression Inventory (BDI) cutoff of 14, indicating “probable depression.” Participants with (BDI≥14; n=15) and without elevated depression symptoms (BDI<14; n=35) were compared on affect- and eating-related variables measured via questionnaire and ecological momentary assessment (EMA) using ANCOVA and mixed model regression. RESULTS: After adjusting for group differences in body mass index (BMI; p=.03), participants with elevated depression symptoms reported greater emotional eating via self-report questionnaire [F(1,50)=4.3; p=.04], as well as more frequent binge eating (Wald chi-square=13.8; p<.001) and higher daily negative affect (Wald chi-square=7.7; p=.005) on EMA recordings. Emotional eating mediated the relationship between depression status and BMI (indirect effect estimate=3.79; 95% CI=1.02–7.46). DISCUSSION: Emotional eating and binge eating were more commonly reported by obese adults with elevated depression symptoms compared to those without, and may occur against a general backdrop of overall low mood. Intervention and prevention programs for obesity and/or depression should address disordered eating to prevent or minimize adverse health consequences.